Conhecimento sobre saúde bucal e práticas desenvolvidas por professores do ensino fundamental e médio - Garbin, Cléa Adas Saliba [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Peruchini, Luís Fernando Dahmer [UNESP]; Martins, Ronald Jefferson [UNESP] (My University, 2013)
Introduction: The oral health education is a process that aims to transform attitudes and behaviors and to form habits for the benefit of individual health. For this to occur, it is necessary to strengthen and continuous repetition, as possible in the school environment. Objective: To analyze teachers’ knowledge about oral health, practices developed in the school environment, as well as the participation of dentists in guiding teachers of primary and secondary schools. Subjects and method: We used a semi-structured questionnaire with open and closed questions about teacher training, received guidance on oral health during their training, development of oral health issues in the classroom and knowledge on the subject . Results: Of the total respondents (n = 221), only 77 (34.8%) said they had guidance on oral health in their training to be a teacher. 70 (31.7%) said they did not develop oral health issues in the classroom and 91 (41.2%) stated no interaction between dentist and professor. We observed deficiency in teachers’ knowledge about certain issues related to dental health. There was statistically significant association between the dentist’s guidance to teachers and the development of oral health actions and the teacher’s knowledge about the location of the first permanent molar eruption (p <0.01). Conclusion: This study conclude that although most educators develop educational practices on oral health in the school environment, there is a deficiency in understanding by teachers of certain subjects, making it necessary a greater participation of the dentist in the transmission of technical and scientific knowledge to them.

Introdução: a educação em saúde bucal é um processo que visa a transformar atitudes e comportamentos e formar hábitos em benefício da saúde do indivíduo. Para que isso ocorra, fazem-se necessários um reforço e uma repetição contínua, possíveis no ambiente escolar. Objetivo: analisar o conhecimento dos professores sobre saúde bucal, as práticas desenvolvidas no ambiente escolar, bem como a participação do cirurgião-dentista na orientação dos professores de ensino fundamental e médio. Sujeitos e método: utilizou-se um questionário semiestruturado, com perguntas abertas e fechadas sobre a formação do professor, orientação recebida sobre saúde bucal, desenvolvimento de temas sobre saúde bucal em sala de aula e conhecimento acerca do assunto. Resultados: do total de entrevistados (n = 221), apenas 77 (34,8%) afirmaram que tiveram orientação sobre saúde bucal na sua formação para professor. Setenta (31,7%) disseram não desenvolver temas sobre saúde bucal em sala de aula e 91 (41,2%) que não existia interação entre dentista e professor. Observou- -se deficiência no conhecimento dos professores sobre determinados assuntos relacionados à saúde bucal. Houve associação estatística significativa entre orienta- ção do dentista aos professores e o desenvolvimento de ações de saúde bucal, bem como o conhecimento do professor sobre o local de erupção do primeiro molar permanente (p < 0,01). Conclusão: apesar de a maior parte dos educadores desenvolver práticas educativas sobre saúde bucal no ambiente escolar, existe defici- ência no entendimento de determinados assuntos pelos professores, fazendo-se necessário maior participação do cirurgião-dentista na transmissão de conhecimentos técnicos e científicos aos educadores.
Oral health knowledge and practices developed by teachers of elementary and secondary local schools
Keywords: Faculty; Knowledge; Health education; Oral health; Docentes; Conhecimento; Educação em saúde; Saúde bucal